Vegetation of the high mountains of the North-East Tuva Republic - Telyatnikov, M. Yu.; Shaulo, D.N.; Prystyazhnyuk, S.A.; Shmakov, A.I. (Acta Biologica Sibirica, 2019)
High-mountain vegetation of North-West Tuva is characterized by great diversity. We identified 10 associations and one subassociation belonging to six classes of the ecological-floristic classification. This is caused by dissimilarity of climatic conditions determined formation of two types of high-mountain landscapes — alpine and goltsy. Other researchers earlier described most of syntaxa. For the first time we described two associations and one subassociation. Сallianthemo sajanensis–Geranietum krylovii ass. nova hoc loco association is placed in Violo altaicae–Festucion krylovianae Ermakov et Zibzeev 2012 prov. provisional alliance and Lagoto integrifoliae–Caricetum ensifoliae ass. nova hoc loco association — in Anemonastro–Festucion ovinae Chytrý et al. 1993 alliance. Both associations are included in Violo altaicae–Festucetalia krylovianae Ermakov et Zibzeev 2012 prov. provisional order of Juncetea trifidi Hadač in Klika et Hadač 1944 class. Communities of Сallianthemo sajanensis–Geranietum krylovii ass. nova hoc loco are restricted to gentle plains and concave moderately steep mountain slopes of various exposures of subalpine and montane-tundra belts of North-West Tuva. Associations Lagoto integrifoliae–Caricetum ensifoliae ass. nova hoc loco are typical of the mountain tundra belt of the humid sector of North-East Tuva and occur on gentle slopes of the mountains and mountain terraces. Subassociation (S.o.–R.q.) pedicularietosum fissae subass. nova hoc loco is placed in Rhodiolion quadrifidae Hilbig 2000 alliance, Rhodioletalia quadrifidae Hilbig 2000 order, Rhodioletea quadrifidae Hilbig 2000 class. Coenoses of (S.o.–R.q.) pedicularietosum fissae subassociation are restricted to the mountain tundra belt of the humid sector of North-East Tuva and occur on the slopes of southern and southwestern exposures. We registered that the high-mountain vegetation of North-East Tyva mainly connected to magmatic acid rocks. The western border of subalpine meadow areas is on the western and southwestern slopes of East Sayanfacing, the Todzha Basin.